Pengaruh Strategi Content Marketing, Engagement Media Sosial Dan Cusstomer Experience Terhadap Loyalitas Pelanggan Pada E- Commerce Tiktok Shop (Studi Kasus Pada Mahasiswa FEB Unisma) - Khatimah, Husnul; Basalamah, Muhammad Ridwan; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to determine the influence of Content Marketing Strategy, Social Media Engagement, and Customer Experience on Customer Loyalty on TikTok Shop E-commerce. Data was taken using purposive sampling from 95 respondents through a questionnaire with the Likert scale. Data analysis was carried out using multiple linear regression and hypothesis tests (F test and t test) with the IBM SPSS 25 program. The results showed that simultaneously, the three variables had a significant influence on customer loyalty (significance 0.000 < 0.05). However, partially, Content Marketing Strategy had no significant effect (significance 0.228 > 0.05), while Social Media Engagement and Customer Experience had a positive and significant effect (significance 0.000 and 0.008 < 0.05). Keywords: Strategies Content Marketing, Social Media Engagement and Customer Experince on Customer Loyalty.